Brothers in Arms - An Experiment on the Alliance Puzzle - Kai A. Konrad; Changxia Ke; Florian Morath (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The generic alliance game considers players in an alliance who fight against an external enemy. After victory, the alliance may break up, and its members fight against each other about the spoils of the victory. Our experimental analysis of this game shows: In-group solidarity vanishes after the break-up of the alliance. Former brothers in arms fight even more vigorously against each other than strangers do. Further, this vigorous internal fighting is anticipated and reduces the ability of the alliance to mobilize joint fighting effort, compared to a situation in which victorious alliance members share equally and peacefully.
Keywords: D72; D74; D70; 330